Length-weight and length-length relationship models of four carangid fishes from the Matang Mangrove Estuaries, Perak, Malaysia - Mohd Khatib, Mohd Azim; Sarker, S. M. Nurul Amin Harmuj Ali; Arshad, Aziz; Md. Yusoff, Fatimah (Universiti Putra Malaysia Press, 2018)
Four species of Carangid fishes from Matang Mangrove Estuaries, Perak, Peninsular Malaysia were selected for the study of length-weight relationships (LWR) and length-length relationships (LLR). A total of 308 individuals were collected from September 2015 to August 2016 by push net (mesh sizes ranges from 2.5 to 5.0 cm). Overall, the growth coefficient (b) values were 2.005, 3.014, 3.452 and 3.194 for Carangoides malabricus, Atule mate, Decapterus macrosoma and Selaroides leptolepis, respectively. Growth coefficient of three species (A. mate, D. macrosoma and S. leptolepis) in the present study were within expected range of 2.5 - 3.5 and this indicated that those species have normal growth pattern. This research serves as the first record of LWR and LLR data for four species of Carangid fishes in the Matang Mangrove Estuaries and surrounding ecosystem, Malaysia.